1995
DOI: 10.1074/jbc.270.35.20550
|View full text |Cite
|
Sign up to set email alerts
|

The Flavin Reductase Activity of the Flavoprotein Component of Sulfite Reductase from Escherichia coli

Abstract: Sulfite reductase (SiR) from Escherichia coli has a alpha 8 beta 4 subunit structure, where alpha 8 is a flavoprotein (SiR-FP) containing both FAD and FMN as prosthetic groups. It also exhibits a NADPH:flavin oxidoreductase activity with exogenous riboflavin, FMN, and FAD serving as substrates. The flavin reductase activity may function during activation of ribonucleotide reductase or during ferrisiderophore reduction. A plasmid containing cysJ gene, coding for the alpha subunit, overexpresses flavin reductase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
1

Year Published

1995
1995
2010
2010

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(60 citation statements)
references
References 21 publications
3
55
1
Order By: Relevance
“…SiR-FP was purified from the ~ overproducing strain as previously described [7]. Protein concentration was estimated by the method of Bradford using bovine serum albumin as a standard [11].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…SiR-FP was purified from the ~ overproducing strain as previously described [7]. Protein concentration was estimated by the method of Bradford using bovine serum albumin as a standard [11].…”
Section: Methodsmentioning
confidence: 99%
“…NADPH-dependent reactions were carried out as previously described [4,7] with 0.25 mM NADPH, an electron acceptor and an appropriate amount of protein. Electron acceptors were present at the following concentrations: 0.1 mM riboflavin, 0.3 mM ferricyanide, 0.2 mM AcPyADP + and 0.1 mM cytochrome c. Absorbance changes were followed using a Kontron Uvikon 930 spectrophotometer at 340 nm for riboflavin and ferricyanide; at 363 nm for AcPyADP ÷ and at 550 nm for cytochrome c. The following extinction coefficients were used: NADPH, ~340 ----6.22 mM -1 -cm-l; AcPyADP +, e363 = 5.6 mM -l .cm-~; reduced cytochrome c, e550 = 22 mM -~.…”
Section: Enzymic Assaysmentioning
confidence: 99%
“…It has been shown that the two SiR-FP flavinic domains can be separated by proteolytic cleavage between Ser217 and Thr220 (Eschenbrenner et al, 1995b). From the properties of the resulting fragments it can be concluded that the N-terminal domain (SiR-FP23) is responsible for the polymerization of the a-chains (Eschenbrenner et al, 1995b) and that the C-terminal monomeric domain (SiR-FP43) is able to catalyze efficient NADPH-dependent reductions of flee flavins (Eschenbrenner et al, 1995a).…”
Section: Introductionmentioning
confidence: 99%
“…From the properties of the resulting fragments it can be concluded that the N-terminal domain (SiR-FP23) is responsible for the polymerization of the a-chains (Eschenbrenner et al, 1995b) and that the C-terminal monomeric domain (SiR-FP43) is able to catalyze efficient NADPH-dependent reductions of flee flavins (Eschenbrenner et al, 1995a). SiR-FP43 belongs to the ferredoxin NADPreductase (FNR) structural family which includes FNR's, phthalate dioxygenase reductase (PDR) (Correll et al, 1992), neutrophil NADPH oxidase and flavin reductases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation